Efficacy and safety of mexiletine in non-dystrophic myotonias: A randomised, double-blind, placebo-controlled, cross-over study - Vicart, Savine; Franques, Jérôme; Bouhour, Françoise; Magot, Armelle; Péréon, Yann; Sacconi, Sabrina; Nadaj-Pakleza, Aleksandra; Behin, Anthony; Zahr, Noël; Hézode, Marianne; Fournier, Emmanuel; Payan, Christine; et al. (Neuromuscular disorders : NMD, 2021)
•Myomex is a randomised, double-blind, placebo-controlled, cross-over study.•It assessed the efficacy and safety of mexiletine in nondystrophic myotonias.•Mexiletine significantly improved stiffness over the 18-day treatment period.•Quality of life was also significantly improved.•Mexiletine is efficient and well-tolerated in nondystrophic myotonias. The MYOMEX study was a multicentre, randomised, double-blind, placebo-controlled, cross-over study aimed to compare the effects of mexiletine vs. placebo in patients with myotonia congenita (MC) and paramyotonia congenita (PC). The primary endpoint was the self-reported score of stiffness severity on a 100 mm visual analogic scale (VAS). Mexiletine treatment started at 200 mg/day and was up-titrated by 200 mg increment each three days to reach a maximum dose of 600 mg/day for total treatment duration of 18 days for each cross-over period. The modified intent-to-treat population included 25 patients (13 with MC and 12 with PC; mean age, 43.0 years; male, 68.0%). The median VAS score for mexiletine was 71.0 at baseline and decreased to 16.0 at the end of the treatment while the score did not change for placebo (81.0 at baseline vs. 78.0 at end of treatment). A mixed effects linear model analysis on ranked absolute changes showed a significant effect of treatment (p < 0.001). The overall score of the Individualized Neuromuscular Quality of Life questionnaire (INQoL) was significantly improved (p < 0.001). No clinically significant adverse events were reported. In conclusion, mexiletine improved stiffness and quality of life in patients with nondystrophic myotonia and was well tolerated.